Investigating the Level of Stability of the Water Zone of Hamon Wetlands Using Sensor Images GEE in MODIS - Mohammad Fartoot Enayat; Kourosh Mohammadpour; Ali Asghar Abdollahi; Bita Jeddi (Nīvār)
International Hamoon wetland has played an important role in social, economic, security, political and environmental activities in southeastern Iran as the 12th residential wetland. In this research, using the Google System inheritance of the Engine and the NDWI Index of Madis Sensor and its verification with Landsat and Satinel satellite imagery 2, the state of blue fluctuations of Hamoon triple wetlands with 1032 images in 2000 to 2022 was investigated The results show that the Hamoon wetland has had the most unstable water conditions compared to two other wetlands, and an average of 31.5 square kilometers, equivalent to 1.3% of its total area in the study period was in dewatering.In other words, 98.8% of its area is dry and alternately 226 months of 18.8 years was completely dry. The maximum water area of this wetland was 7.3% of its total area during this period of 183 square kilometers. Also, the Hamon wetland with the average of 243.7 square kilometers of 243.7 square kilometers equivalent to 15.6% of the total area of the wetland in the study period has been the most stable blue conditions, and in this period 194 months, 16.2 years has been alternately watered. Is. Also, the highest area of the wetland was recorded at 797 square kilometers of 51.1% of its total area in 2020. This dewatering level in the dried area of northern Sistan and Baluchestan, which is 50 mm aggregates, can be an important source of water supply.